Social Media im transnationalen Alltag: Zur medialen Ausgestaltung sozialer Beziehungen zwischen Deutschland und Senegal - Pfeifer, Simone (transcript, 2019)
What role do digital media play in transnational social life? A research contribution on the relationship between migration and the media.